THE FRAGILITY OF DREAM IN JOHN STEINBECK'S OF MICE AND MEN; A GENETIC STRUCTURALISM APPROACH - SETYORINI , SETYORINI (2007)
The researches intends to find out how the fragility of dream is reflected in John Steinbeck's of Mice and Men. The research consists of two objectives, namely to analyze the novel based on its structural elements and to analyze the novel based on the genetic structuralism approach. The research paper uses qualitative type. The data sources are taken from two sources, namely the text of the novel as primary source and other materials related to problem of the study. The method of data collection is library research, and the technique of data analysis is descriptive. The result of the research is that during the great depression many people in America have the dream to be better and it is called as the American Dream. Of Mice and Men is one of the American novels that reflect to the American Dream. The fragility of dream becomes the social phenomena in most of the working class in America because of their social status as the lower class that doesn't have position, skill, money and family. They are always ignored by people from the upper class.